Colon cancer survival differs from right side to left side and lymph node harvest number matter - Lucia Mangone; Carmine Pinto; Pamela Mancuso; Marta Ottone; Isabella Bisceglia; Giorgio Chiaranda; Maria Michiara; Massimo Vicentini; Giuliano Carrozzi; Stefano Ferretti; Fabio Falcini; Cesare Hassan; et al. (BMC, 2021)
Abstract Background Right-sided colorectal cancer (CRC) has worse survival than does left-sided CRC. The objective of this study was to further assess the impact of right-side location on survival and the role of the extent of lymphadenectomy. Methods All CRCs diagnosed between 2000 and 2012 in Emilia-Romagna Region, Italy, were included. Data for stage, grade, histology, screening history, and number of removed lymph nodes (LN) were collected. Multivariable Cox regression models were used to estimate hazard ratios (HR), with relative 95% confidence intervals (95%CI), of right vs. left colon and of removing < 12, 12-21 or > 21 lymph nodes by cancer site. Results During the study period, 29,358 patients were registered (8828 right colon, 18,852 left colon, 1678 transverse). Patients with right cancer were more often older, females, with advanced stage and high grade, and higher number of removed LNs. Five-year survival was lower in the right than in the left colon (55.2% vs 59.7%). In multivariable analysis, right colon showed a lower survival when adjusting for age, sex, and screening status (HR 1.12, 95%CI 1.04-1.21). Stratification by number of lymph nodes removed (12-21 or > 21) was associated with better survival in right colon (HR 0.54, 95%CI 0.40-0.72 and HR 0.40, 95%CI 0.30-0.55, respectively) compared to left colon (HR 0.89, 95%CI 0.76-1.06 and HR 0.83, 95%CI 0.69-1.01, respectively). Conclusions This study confirms that right CRC has worse survival; the association is not due to screening status. An adequate removal of lymph nodes is associated with better survival, although the direction of the association in terms of causal links is not clear.